Heterogeneous oxidation of hydrazine by barium chromate - Baumgartner, Erwin C.; Blesa, Miguel Ángel; Larotonda, Ricardo M.; Maroto, Alberto Jorge Gerarado (Royal Chemical Society, 1985)
Fil: Baumgartner, Erwin C. Comisión Nacional de Energía Atómica; Argentina